Legal Culture and Law Enforcement in Indonesia: A Normative Juridical Perspective - Mardalena Hanifah; Muhammad Adil (Eduvest - Journal of Universal Studies, 2025)
Legal culture plays a very important role in law enforcement because the law is heavily influenced by the legal culture in the form of values, views, and attitudes within society. Therefore, legal culture and law enforcement are two interconnected elements. One of the problems currently faced by the Indonesian nation is the low legal culture among its citizens. This is clearly reflected in the situations that are currently prevalent in Indonesia. The method in this study is library research, which involves collecting data through scientific literature. The results of this study are as follows: First, legal culture is the overall attitude of citizens, which is general in nature, along with societal values that determine how the law should apply in society; Second, the characteristics of legal culture include public awareness of the importance of law as a foundation for just and orderly community life; Third, the application of legal culture is crucial in the context of international relations, as each country has a different legal system, and understanding and appreciating the legal culture of other countries will facilitate cooperation and relations between nations.